Does Local Capital Supply Matter for Public Firms’ Capital Structures? - Adhikari, Binay K.; Cicero, David C.; Sulaeman, Johan (Journal of Financial and Quantitative Analysis, 2021)
Abstract Publicly listed firms respond to capital supply conditions shaped by local investing preferences. Public firms headquartered in areas with higher proportions of senior citizens and women use more debt financing. These demographics are associated with conservative investing, leading to a higher and more stable local supply of debt capital. The demographics–leverage relation is more pronounced for firms that cannot easily tap public bond markets, which is the majority of public firms. Changes in firms’ financing activities around exogenous shocks to credit supplies, including interstate banking deregulation and the 2008–2009 financial crisis, support the local capital supply hypothesis.